A Secure & Smart Shopping System: A Review - Borse, Janhavi; Raut, Harshada; Divate, Priyanka; Tungar, Sujata; Patil, Meghna (International Journal of Computer Sciences and Engineering, 2018)
With the recent emergence of social E-commerce the act of shopping is evolving. The physical shopping destination like commercial shopping Center, Wall-Mart's, supermarket also seek smartly and securely in shopping experience. Consumers with QR (Quick Response) code applications, RFID tag, Zig-Bee system, NFC systems can find a modernistic way of buying the products and goods. It collects knowledge about the technical details, working and pros and cons of individual technique as me The paper represent aforementioned techniques that can be deployed for smart shopping experience mentioned previously. The study is carried out to help new user for selecting particular technique in his area of do main